Analisis Dan Pengujian Sistem Pada Aplikasi Todo Berbasis Php Menggunakan Metode Agile Dan Black-box Testing - Khusnul Fikroh Adillah; Kaysha Jasmine; Chairul Anwar (PT Jurnal Cendekia Indonesia, 2025)
System testing is an essential stage in software development to ensure that the system operates according to user needs and is free from errors. This study aims to test and evaluate the functional quality of the Todo-PHP application, a webbased task management system built using PHP and MySQL. The application was selected due to its open-source nature and early-stage development, making it relevant for identifying and analyzing potential bugs. The development method used is Agile, which is iterative and adaptive to change. This approach is considered suitable for small-scale projects like Todo-PHP, as it supports continuous improvement and testing. To test the system’s functionality, the black-box testing method was applied, which focuses on evaluating input and output without analyzing the internal structure of the code. The test was conducted on core features such as login, task management, password change, and account deletion. The testing was performed in a local environment using a PHP server and a MySQL database. The results showed that most features performed as expected, although several minor issues were found, such as suboptimal input validation and buttons that did not respond under certain conditions. These findings served as a basis for further development recommendations.This study is expected to provide a practical overview of system testing implementation and contribute to improving the quality of open-source applications like Todo-PHP.